How great is the threat of chikungunya virus?. Issue 3 (March 2015) - Waggoner, Jesse J; Pinsky, Benjamin A
<x xml:space="preserve">Abstract</x> In the last decade, chikungunya virus has emerged from an obscure arbovirus that caused limited outbreaks of disease in Africa and Asia to the cause of a pandemic affecting millions of people and spanning five continents. Two separate chikungunya virus genotypes have been responsible for outbreaks during this period, including strains adapted to transmission in Aedes albopictus mosquitoes. Further spread of this virus into new regions of the Western Hemisphere is predicted during the present rainy season in the tropics, and recurrent viral introductions and disease outbreaks, as occurred in Réunion in 2010, should be expected. Chikungunya virus no longer simply threatens; it has arrived as a significant, global pathogen.